PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE TRUE OR FALSE STATEMENT TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII.2 DAN VIII.3 SMPN 27 PADANG - Melvasari, Hutri; Zulfaneti, Zulfaneti; Yunita, Alfi (STKIP PGRI Sumbar, 2013)
This research is motivated by the students understanding of mathematical concepts are still low. This study aims to determine whether students understanding of mathematical concepts by applying active learning strategy Type True Or False Statement better than students understanding of mathematical concepts with the application of conventional learning. This type of research is experimental, the research design pre eksperimental design : static group comparison. The population in this research is the students in grade VIII SMPN 27 Padang. Sampling was done by purposive sampling, with the consideration that both classes have an average that is similar to the decision classes VIII.2as eksperimental and VIII.3 as control. The instruments that are used in this study are studentsâ activity observation sheet and essay test. Based on the result of the study, it is found that increasing percentage in each meeting. Results of data analysis that the two classes are normally distributed and homogeneous samples and t test results obtained P-value=0,003 is less than Î±=0,05, so that hypothesis is approved. It can be concluded that the students understanding of mathematical concepts by applying active learning strategy Type True Or False Statement VIII.2 grade better than students understanding of mathematical concepts by applying conventional learning models VIII.3 grade SMP 27 Padang